Elephant Hunters Inspecting Concrete Sidewalks: Engineering Expertise in Toronto’s Age of Municipal Reform - Hull, James (Ontario History, 2008)
Criticisms of the work of the City Engineer’s department by members of Toronto Council in 1891-92 led variously to an action for libel, an inquiry, and resignations. While urban reformers in Ontario and elsewhere often couched their criticisms in terms of rational expertise vs. political interference, what this particular case and others like it show instead is that the possession of expert knowledge and the appropriation of a mantle of scientific rationality did not remove politics from decision-making but rather made salient the essentially political nature of expertise. These incidents and the documentation they generated allow us particularly useful windows through which we may view the evolution of municipal governance during a crucial period in the history of North American cities.